Particulate adjuvants for use in cancer vaccination - Ward, Ross (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2023)
It is estimated that 1 in 2 people will develop cancer in their lifetime, highlighting the urgent need for improved preventative and therapeutic strategies. Cancer immunotherapy has emerged as a key pillar of cancer treatment, and in this context, both prophylactic and therapeutic cancer vaccines have shown significant promise as standalone therapies or in combinatorial approaches with checkpoint blockade therapy. However, the development of such vaccines has been hindered by a lack of adjuvants that effectively drive protective cell mediated immunity (CMI), coupled to poorly defined adjuvant mechanisms of action (MOA), arising from empirical adjuvant development instead of rational design. The size of particulate adjuvants has emerged as a key parameter influencing adjuvanticity, and polymeric nanoparticles (NP) of approximately 50nm in diameter are promising adjuvants capable of eliciting CMI. However, there are outstanding questions relating to nanoparticle adjuvant MOA and the functionality of adjuvant induced T cell responses. Research in the Lavelle Lab has identified highly deacetylated chitin-derived polymers as potent CMI driving adjuvants, with adjuvanticity associated with potent activation of STING and IFNAR signalling. As a result, both 50nm NPs and highly deacetylated chitin-derived polymers are promising adjuvant candidates for use in cancer vaccine approaches and this project aims to characterise their efficacy and further their rational design through providing insights into their MOA. This work has identified components of the canonical and non-canonical inflammasomes, particularly caspase 11 as essential to 50nm NP adjuvanticity, providing crucial mechanistic insights into how size is instructive in mediating particle induced CMI. Crucially, intramuscular vaccination with 50nm NP was shown to promote protective anti-tumour immunity in prophylactic and therapeutic tumour challenge settings, largely dependent on the induction of CD8+ T cells. In addition, this work has characterised the C100 (100% deacetylated chitin) polymer as a potent adjuvant for use in intratumoral vaccination approaches. This anti-tumour therapeutic efficacy of C100 was dependent on STING and IFNAR signalling, with CD8+ T cells characterised as cellular mediators of protection. Vaccination with either C100 or 50nm polystyrene NP adjuvants was shown to synergise with PD-1 checkpoint blockade in eliciting anti-tumour immunity, highlighting the possibility of future combinatorial therapeutic strategies. Altogether this project has furthered the rational design of two vaccine adjuvants with potential application in cancer vaccine approaches.
APPROVED
Keywords: Adjuvants; Vaccines; Cancer; Cell mediated immunity; CD8 T cells; Non-canonical inflammasome; Caspase 11; cGAS-STING; Pyroptosis; Gasdermins; Adaptive Immunity; Immunotherapy